(untitled) (Revista Innova Educación, 2021)
The development of creative thinking must be considered as a necessity in pedagogical practice in every educational system. The objective of this article was to present some concepts and strategies that are being developed in the classrooms. The methodology used was the experimental documentary technique. In addition, a search was done for articles of a scientific nature, published in various reliable databases. Concluding that, creative thinking is a capacity that the person must possess in the 21st century. Therefore, every student must develop it to produce innovative ideas that allow them to solve problematic situations.